Human rights : the hard questions - Holder, Cindy; Reidy, David (New York : Cambridge University Press, 2013)
The United Nations General Assembly adopted the Universal Declaration of Human Rights in 1948. A burgeoning human rights movement followed, yielding many treaties and new international institutions and shaping the constitutions and laws of many states. Yet human rights continue to be contested politically and legally and there is substantial philosophical and theoretical debate over their foundations and implications. In this volume distinguished philosophers, political scientists, international lawyers, environmentalists and anthropologists discuss some of the most difficult questions of human rights theory and practice: What do human rights require of the global economy? Does it make sense to secure them by force? What do they require in'jus post bellum' contexts of transitional justice? Is global climate change a human rights issue? Is there a human right to democracy? Does the human rights movement constitute moral progress? The book focuses on hard, unresolved questions ; Is not merely an introductory survey of what is already established ; Puts legal, philosophical and anthropological points of view in conversation ; Addresses a broad range of discussion, including the global economy, jus post bello contexts and global climate change. -- From publisher's website.
What Are Human Rights? -- Human rights and human nature / Chris Brown -- Universalism and particularism in human rights / Neil Walker -- Are human rights universal? / Rex Martin. -- How do Human Rights Relate to Group Rights and Culture? -- The significance of cultural differences for human rights / Alison Dundes Renteln -- Groups and human rights / Peter Jones -- Entangled: family, religion and human rights / Ayelet Shachar -- What does cultural difference require of human rights? / Claudio Corradetti. -- What do Human Rights Require of the Global Economy? -- What do human rights require of the global economy? : beyond a narrow legal view / Adam Mcbeth -- Universal human rights in the global political economy / Tony Evans -- Human rights and global equal opportunity: inclusion not provision / Ann E. Cudd. -- How do Human Rights Relate to Environmental Policy? -- Human rights in a hostile climate / Stephen M. Gardiner -- A human rights approach to energy, poverty and gender inequality / Gail Karlsson -- Pollution wolves in scientific sheep's clothing: why environmental-risk assessors and policy-makers ignore the'hard issues' of the human rights of pollution victims / Kristin Shrader-Frechette. -- Is There a Human Right to Democracy? -- Is there a human right to democracy? / Hilary Charlesworth -- The human right to democracy and its global import / Carol C. Gould -- An egalitarian argument for a human right to democracy / Thomas Christiano. -- What Are the Limits of Rights Enforcement? -- Is it ever reasonable for one state to invade another for humanitarian reasons? : the'declaratory tradition' and the UN Charter / Julie Mertus -- Conflicting responsibilities to protect human rights / Larry May -- Searching for the hard questions about women's human rights / Marysia Zalewski -- Are human rights possible after conflict? : diary of a survivor / Evelyn Amony and Erin Baines -- Moral progress and human rights / Allen Buchanan -- Human rights and moral agency / Mark Goodale -- Gender mainstreaming human rights: a progressive path for gender equality? / Laura Parisi -- Rights, practice, reality, and hope: hard questions about human rights / Cindy Holder and David Ready.
Includes bibliographical references and index.
Keywords: Human rights